2020
DOI: 10.1590/1678-4766e2020008
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic matching in ovipositor size in the parasitoid Galeopsomyia sp. (Hymenoptera, Eulophidae) attacking different gall inducers

Abstract: ABSTRACT Parasitoid ovipositor size importantly affects host choice; those attacking exposed hosts usually have shorter ovipositors compared to those needing drilling deeper through substrates such as plant tissue and gall tissue. Most studies treat this theme at the interspecific level, and the aim of this work was to test for intraspecific variation and phenotypic matching in ovipositor size for Galeopsomyia sp. attacking galls. Galls were sampled from Guapira opposita(Nyctaginaceae), a host plant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Conversely, wasps with longer ovipositors (Torymidae and Braconidae), interacted with larger and thicker galls as those produced by Bruggmannia sp.2 and P. brasiliensis. Also, parasitoids with variable ovipositor sizes, such as Galeopsomyia sp., were able to attack a range of galls (Luz et al, 2020). Stone and Schönrogge (2003) mention gall morphology as one of the main factors influencing gall inducer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, wasps with longer ovipositors (Torymidae and Braconidae), interacted with larger and thicker galls as those produced by Bruggmannia sp.2 and P. brasiliensis. Also, parasitoids with variable ovipositor sizes, such as Galeopsomyia sp., were able to attack a range of galls (Luz et al, 2020). Stone and Schönrogge (2003) mention gall morphology as one of the main factors influencing gall inducer interactions.…”
Section: Discussionmentioning
confidence: 99%
“…(Van Hezewijk & Roland, 2003). Moreover, Luz et al (2020) suggested phenotypic matching for the increased size and ovipositor length of Galeopsomyia sp. attacking the thicker galls of two cecidomyiid Bauhinia spp.…”
Section: Discussionmentioning
confidence: 99%
“…This result differs from what is found in the literature. Luz et al (2020) found clear evidence that a model considering morphological coupling between Cecidomyiidae gall wall thickness and parasitoid ovipositor length was the best one to explain interaction network structure on the host plant Guapira opposita . For oak galls, despite parasitoid polyphagy, there is evidence that parasitoid community structure is defined by various attributes of galls such as hardness, hairiness and adhesion (some galls secrete sticky substances) (Bailey et al, 2009).…”
Section: Discussionmentioning
confidence: 99%